Types of Moral Values in “Ralph Break The Internet Wreck It Ralph 2” - Made Suarjana; Ni Made Verayanti Utami; I Gusti Ayu Vina Widiadnya putri (Institut Pariwisata dan Bisnis Internasional, 2024)
This study aims to determine the types of Moral Values and the context of the situation when delivering the types of moral values expressed in the film